Hollow-cone Foucault imaging method. (13th March 2019) - Harada, Ken; Kawaguchi, Atsushi; Kotani, Atsuhiro; Fujibayashi, Yukihiro; Shimada, Keiko; Mori, Shigeo
Abstract: A hollow-cone Foucault (HCF) imaging method using Lorentz microscopy was developed. Hollow-cone illumination was realized by using deflectors above the specimen and an inclined electron beam circulating with respect to the optical axis. The advantage of the HCF method, having the bright and dark-field modes, is that it can simultaneously visualize both magnetic domains and magnetic domain walls under the in-focus condition. Furthermore, schlieren images, obtained under the specific inclination angle of the illumination beam by adjusting the angle between the bright-field and dark-field modes, can qualitatively visualize the electromagnetic fields in spaces around the specimen.